The Role of Roadside Tree Planting in Environmental Conservation - Waheed, Muhammad; Zunaira Naeem (RADINKA JAYA UTAMA PUBLISHER, 2024)
Roadside tree planting refers to the practice of planting trees along roadsides and highways. It serves multiple purposes, including enhancing the aesthetic appeal of the landscape, providing shade, reducing erosion, improving air quality, and creating wildlife habitats. These trees can also act as windbreaks, reducing the impact of strong winds on vehicles and nearby properties. Moreover, they contribute to mitigating the urban heat island effect by providing cooling shade and reducing surface temperatures. Additionally, roadside tree planting can help in carbon sequestration, as trees absorb carbon dioxide from the atmosphere during photosynthesis. Overall, it's a sustainable practice with numerous environmental, social, and economic benefits.